Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.1016/j.paid.2015.07.028
|View full text |Cite
|
Sign up to set email alerts
|

Individual differences in prophetic dream belief and experience: Exploring demographic and sleep-related correlates

Abstract: A large proportion of the general population believes that dreams can provide information about future events that could not have been obtained by any known means. The present study identifies several factors associated with prophetic (precognitive) dream belief and experience. Participants (N = 672) were measured on demographic variables, sleep characteristics, and precognitive dream (PD) belief, experience, and frequency. Three 'sleep clusters' were identified based on the analysis of the sleep-related varia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…Traumatic experiences are frequently linked to poorer sleep quality, higher frequency of nightmares, sleep paralysis, vivid and lucid dreams, OBEs, and potentially precognitive dreams (e.g., Aviram & Soffer-Dudek, 2018; Giannakopoulos & Kolaitis, 2021; Valášek & Watt, 2015). However, several indicators suggest increased prevalence of atypical dream states among the NDE group in this study were primarily associated with the NDE, rather than the event of coming close to death.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Traumatic experiences are frequently linked to poorer sleep quality, higher frequency of nightmares, sleep paralysis, vivid and lucid dreams, OBEs, and potentially precognitive dreams (e.g., Aviram & Soffer-Dudek, 2018; Giannakopoulos & Kolaitis, 2021; Valášek & Watt, 2015). However, several indicators suggest increased prevalence of atypical dream states among the NDE group in this study were primarily associated with the NDE, rather than the event of coming close to death.…”
Section: Discussionmentioning
confidence: 99%
“…Despite their apparent ubiquity, precognitive dreams are not well understood, are little studied, and are often relegated to the domain of parapsychology, perhaps due to their ostensible contradiction of established scientific laws and principles. Like other types of unusual dreams, an increased prevalence of precognitive dreaming has been linked to stress and trauma, specifically childhood trauma and poor sleep quality (Sar et al, 2014; Valášek & Watt, 2015).…”
Section: Dreams Influences On Dreaming and Atypical Dream Statesmentioning
confidence: 99%
“…When compared with males, females elicited higher scores in Dream omen and health, Dream superstition, Dream meaninglessness, and Dream reality; males and female showed similar scores in Dream Attitude. Females were more likely to agree that dreams had special functions, such as foretelling the future and reflecting mental and physical health, 27,46,55 which was the exact was the content of the Dream omen and health dimension. This study observed the same phenomenon.…”
Section: Gender Differencementioning
confidence: 99%